Investor Attention and the Religious Sentiment: Empirical Evidence from Ramadan Return on the Indonesia Stock Exchange - Kris Brantas Abiprayu; Dwi Cahyaningdyah; Salsabila Nadianisa Maruto; M. Iqrar Nusa Bhakti (Management Analysis Journal, 2024)
This study explores the influence of investor attention and religious sentiment—specifically during the holy month of Ramadan—on stock returns in the Indonesian capital market. Using the Market Attention Index (MAI), derived from Google Search Volume data, we examine how elevated public focus corresponds with return anomalies across 100 stocks from both syariah-compliant (ISSI) and conventional (LQ45) indices during the 2020–2023 Ramadan periods. Regression analysis reveals a statistically significant and positive relationship between MAI and intraday stock returns, underscoring the role of behavioral attention in asset pricing. Furthermore, dummy variables for specific Ramadan days—the 10th and 25th—also show positive return effects, supporting the notion that heightened religiosity and mood uplift during spiritually significant days influence investor sentiment. These findings align with behavioral finance theories and enrich prior research on the “Ramadan Effect” and “Holy Day Effect.” The results offer practical implications for trading strategies and policy design in Muslim-majority markets. By integrating digital behavior metrics and religious calendar events, this study contributes a novel framework for understanding asset price fluctuations during culturally sensitive periods in emerging markets.